(untitled) (Scientific journal of the Fergana State University, 2025)
In the article, the sorption isotherm in diglycidylthiocarbamide and melamine-based complex-forming ionite is studied on the example of Cu (II) ions. As a result of the research, it was determined that the sorption isotherm obeys the Freundlich model at lower temperatures. Accordingly, constants of sorption isotherms of Cu (II) ions in the synthesized ionite were calculated according to the Freundlich model. Cu (II) ion self-sorption in the synthesized ionite with decrease in free energy and enthalpy, increase in entropy, formation of coordination compounds in the ionite phase, increase in entropy of the system is based on decomposition of solvate clouds of ionite active functional groups.